Missed Diagnosis and Acute Management of Radial Head Dislocation With Plastic Deformation of Ulna in Children. Issue 4 (April 2020) - Singh, Vivek; Dey, Sukalyan; Parikh, Shital N.
Abstract : Background: Radial head dislocation with ulnar bowing (Monteggia type I equivalent injury) is a frequently missed injury. If not recognized acutely, these missed injuries can lead to serious long-term complications. The purpose of this study was to evaluate the rate of missed diagnosis and to report on the characteristics and early management of this specific injury pattern. Methods: A total of 112 patients with Monteggia fracture-dislocation were identified, of which 18 patients had sustained a Monteggia type I equivalent injury. The total duration between injury, diagnosis, and treatment was noted. Medical records were reviewed to identify cases with the initially missed diagnosis. The radiographic assessment included the direction of radial head dislocation and location/displacement of the apex of the ulnar bow. Clinical outcomes were evaluated using Kim elbow performance score. Results: Thirteen of 18 cases with Monteggia equivalent injury were missed at the initial presentation. The diagnosis was established when the patients followed up in the orthopaedic clinic. Of these 18 patients, 11 were treated by closed reduction/cast and 7 patients required surgery. Significant differences were found between the closed reduction/cast and operative group for the mean time from injury to treatment (3.2±2.6 vs. 12.7±13.6 d). For each day of delay in treatment, the odds for surgical intervention increased by a factor of 1.126 (12.6%). There were no significant differences between the location and magnitude of the apex of the ulnar deformity between the 2 groups. Kim elbow score was excellent in all cases at the latest follow-up. Conclusions: Clinical suspicion and careful radiographic assessment are of utmost importance for every child with forearm and elbow injury without an apparent fracture, as there is a high rate of missed diagnosis for this specific Monteggia injury pattern. Prompt treatment would allow for successful closed reduction while even minor delays would increase the need for surgical intervention. Level of Evidence: Therapeutic, level III.